DEVELOPING PRAGMATIC COMPETENCE OF INDONESIAN EFL LEARNERS THROUGH TEACHING SPEECH ACTS OF ORAL AND WRITTEN COMPLAINTS - Waliyadin Nuridin (Universitas Islam Negeri Banda Aceh, 2018)
The lack of pragmatic competence could result in unexpected effects on the speakers; for example, the speakers are considered as rude and aggressive people. Accordingly, developing pragmatic competence for EFL learners should be a great concern. This article is aimed to fill in the needs of pragmatic teaching by providing examples of teaching practices that could be used to develop EFL learners’ pragmatic competence. There are two tasks that have been designed by drawing on discourse processing framework proposed by Celce-Murcia and Olshtain (2000) to achieve the production of both written and spoken discourses. The first task is on speaking, particularly on the speech act of oral complaints. The second task is on writing a letter of complaint. This article suggests that developing pragmatic awareness through the speech act of oral and written complaints is desirable.